Respuesta :

Answer:

Step-by-step explanation:

Differentiate using the power rule

[tex]\frac{d}{dx}[/tex] (a[tex]x^{n}[/tex] ) = na[tex]x^{n-1}[/tex]

Given

[tex]\frac{1}{4}[/tex] [tex]x^{4}[/tex], then

[tex]\frac{d}{dx}[/tex] ( [tex]\frac{1}{4}[/tex] [tex]x^{4}[/tex] )

= 4 × [tex]\frac{1}{4}[/tex] [tex]x^{4-1}[/tex] = x³

Answer:

x^3.

Step-by-step explanation:

Algebraic differentiation:

If y = ax^n , dy/dx = an x^(n-1), so

y = x^4 / 4

  = (1/4)x^4  

dy/dx = (1/4 * 4) x(4-1)

= x^3.